Does Omnibus Law Affect the Indonesian Investment Regulations towards Chinese Investors? - M. Iqbal; M. Misbahul Mujib; Yuliannova Lestari (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2022)
This paper examined the polemic of Indonesian omnibus Law that affect the international market interest in Indonesia, especially for the Chinese investor. On the one hand, this act and its implementation act give hope for a more conducive climate for foreign investment. On the other hand, it also invites resistance from various components of the nation due to the non-transparent procedure of its formation. It substantively degrades the interests of the wider community and is more in favour of the interests of investors. This research comes up with the liberal institutionalism theory; when state elites do not predict self-interested benefits from cooperation, it means no expectation of cooperation to occur, nor the institutions that facilitate cooperation to develop. On the other hand, when states can jointly benefit from cooperation, governments expect to attempt to establish such an institution. . As a result, Omnibus Law affects ambiguity and uncertainty for foreign investor especially for Chinese. However Omnibus Law is still uncertain and ambiguous; in reality the foreigner investment especially Chinese Investments in Indonesia is still run well and tend to increase. It is because Constitutional Court's decision did not invalidate 47 government regulations and 4 presidential regulations derived from the Job Creation Law. In addition, from the perspective of liberal Institutionalism, it has been long time Indonesia and China has built diplomacy for continuous mutual cooperation.